A Study on Emotional Maturity of College Students - G. Visvanathan, K. Subbarayan* (Recent Research in Science and Technology, 2011)
The Emotional maturity becomes important in the behaviour of individuals. As the students are the pillars of the future generations their Emotional maturity is vital one. So the present study intends to measure the Emotional Maturity of college students. Normative survey method and random sampling technique has been used in the present study. The Ã¢â‚¬Å“Emotional Maturity ScaleÃ¢â‚¬Â standardized by K.M.Roma Pal [5] was used for this study. The result of the study shows that the emotional maturity of college students is extremely unstable.